Cancer risk of arc welders exposed to fumes containing chromium and nickel. - Becker, Nikolaus; Claude, Jenny; Frentzel-Beyme, Rainer (Scandinavian Journal of Work, Environment & Health, 1985)
A retrospective follow-up study among chromium- and nickel-exposed welders, which took into consideration welding procedures, duration of exposure, and smoking habits, yielded an increased cancer risk in a comparison with an internal reference group of turners, milling cutters, and drillers, as well as in a comparison with the general population of the Federal Republic of Germany. Due to the cohort size (1 224 welders, 1 694 turners) and the fact that the observation period is still too short, confirmed statements as to the target cancer sites cannot yet be made. However, it emerges that welding with coated electrodes shows a higher cancer risk as compared to the other welding processes observed. This finding may be explained by the fact that the share of hexavalent chromium compounds in the welding fumes is greater with coated electrodes than with other processes so that a follow-up study observing the health risks of chromium and nickel fumes separately would be warranted. For the confirmation of a more favorable outcome with gas-shielded welding, a larger investigation group or a longer observation period would be required.